Preeclampsia and Increased Permeability Over the Blood–Brain Barrier: A Role of Vascular Endothelial Growth Receptor 2. (31st August 2020) - Bergman, Lina; Acurio, Jesenia; Leon, Jose; Gatu, Emily; Friis, Therese; Nelander, Maria; Wikström, Johan; Larsson, Anders; Lara, Evelyn; Aguayo, Claudio; Torres-Vergara, Pablo; Wikström, Anna-Karin; et al.
Abstract: BACKGROUND: Cerebral complications in preeclampsia are leading causes of maternal mortality worldwide but pathophysiology is largely unknown and a challenge to study. Using an in vitro model of the human blood–brain barrier (BBB), we explored the role of vascular endothelial growth factor receptor 2 (VEGFR2) in preeclampsia. METHODS: The human brain endothelial cell line (hCMEC/D3) cultured on Tranwells insert was exposed (12 hours) to plasma from women with preeclampsia ( n = 28), normal pregnancy ( n = 28), and nonpregnant ( n = 16) controls. Transendothelial electrical resistance (TEER) and permeability to 70 kDa fluorescein isothiocyanate (FITC)-dextran were measured for the assessment of BBB integrity. We explored possible underlying mechanisms, with a focus on the expression of tight junction proteins and phosphorylation of 2 tyrosine residues of VEGFR2, associated with vascular permeability and migration (pY951) and cell proliferation (pY1175). Plasma concentrations of soluble FMS-like tyrosine kinase-1 (sFlt-1) and placental growth factor (PlGF) were also measured. RESULTS: hCMEC/D3 exposed to plasma from women with preeclampsia exhibited reduced TEER and increased permeability to 70 kDa FITC-dextran. These cells upregulated the messenger ribonucleic acid (mRNA) levels of VEGFR2, and pY951-VEGFR2, but reduced pY1175-VEGFR2 ( P < 0.05 in all cases). No difference in mRNA expression of tight junction protein was observed between groups. There was no correlation between angiogenic biomarkers and BBB permeability. CONCLUSIONS: We present a promising in vitro model of the BBB in preeclampsia. Selective tyrosine phosphorylation of VEGFR2 may participate in the increased BBB permeability in preeclampsia irrespective of plasma concentrations of angiogenic biomarkers.